KHITOBAH AND SELF-DEVELOPMENT MANAGEMENT: A STRATEGIC APPROACH TO BOOSTING STUDENTS' SELF-CONFIDENCE - Kholil, Muhammad; Fuada, Shofiya; Suhermanto, Suhermanto (Managere: Indonesian Journal of Educational Management, 2023)
This research aims to analyze and examine development strategies through sermons to increase students' self-confidence in their speaking skills and determine what obstacles students face when performing sermons. This research was conducted at the MI Ma'arif Al-Ishlah Kalisat Bungkal Ponorogo institution. Researchers used a qualitative case study type approach. Data was collected using interview, observation and documentation techniques and then analyzed through several steps: data collection, data reduction, data presentation and conclusions. The results of the research show that (1) Efforts that need to be made by a teacher to increase students' self-confidence are to encourage, guide well and provide motivation to MI Nurul Ulum students who take part in khutbah activities. (2) The main obstacle teachers and MI Nurul Ulum face is that students need more reparation in sermon activities. This lack of student preparedness resulted in a lack of focus while appearing on stage, and there were even cases where some students brought texts when they came to the stage. Meanwhile, the obstacles students face in giving sermons vary, for example, lack of self-confidence, stage fright, nervousness about speaking in public and fear of making mistakes. Because they only pay attention and listen to what other students say, which causes the role of the sermon not to fail too well.